TIGA PILAR BUDAYA CIANJUR: ETIK, ESTETIK, KINESTETIK - Wiradiredja, Moch. Yusuf; Resmana, Oman (LP2M ISBI Bandung, 2023)
Character Education is an educational movement under the responsibility of the education unit to strengthen the character of students through the harmonization of heart, taste, mind, and sports. The end of strengthening character education is none other than to build the nation's identity and competitiveness. The three pillars of Cianjur culture in the form of ngaos, mamaos, maenpo, as one of the cultural and artistic expressions as the nation's identity have values that build the spirit of character education, that represent ethic, aesthetic, and kinestethic. This can be seen from the elements contained in it, where in addition to national identity, there are also noble cultural ethical values, including the value of art that accommodates the heart, taste, mind and body. Thus, the involvement of local values in the character education movement is an appropriate effort. This research focuses on this effort, especially in mapping the relationship between the three pillars of Cianjur culture and the conception of character education